If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -7b = 18 + -9b Solving 12 + -7b = 18 + -9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '9b' to each side of the equation. 12 + -7b + 9b = 18 + -9b + 9b Combine like terms: -7b + 9b = 2b 12 + 2b = 18 + -9b + 9b Combine like terms: -9b + 9b = 0 12 + 2b = 18 + 0 12 + 2b = 18 Add '-12' to each side of the equation. 12 + -12 + 2b = 18 + -12 Combine like terms: 12 + -12 = 0 0 + 2b = 18 + -12 2b = 18 + -12 Combine like terms: 18 + -12 = 6 2b = 6 Divide each side by '2'. b = 3 Simplifying b = 3
| 4x+8y=-44 | | ax+5=bx-cforx | | 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 | | 10-3c=10+9c | | 1x+7=2x+3 | | 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 | | 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 | | 6p+5=17 | | 2(x^2-7x+21)=0 | | 502.4=3.14(4)h | | Y-x=-9 | | 30+x=167 | | .5(2n-3)-.1=.4(6+2n) | | 5*8+6y=94 |